2016
DOI: 10.1590/1414-431x20165620
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a fusion plasmid containing the PSCA gene and cytotoxic T-lymphocyte associated antigen-4 (CTLA-4) and its anti-tumor effect in an animal model of prostate cancer

Abstract: Cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) is a negative regulator of T cell activation, which competes with CD28 for B7.1/B7.2 binding, and which has a greater affinity. Fusion of specific antigens to extracellular domain of CTLA4 represents a promising approach to increase the immunogenicity of DNA vaccines. In this study, we evaluated this interesting approach for CTLA4 enhancement on prostate stem cell antigen (PSCA)-specific immune responses and its anti-tumor effects in a prostate cancer mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Notably, PSCA is considered as an effective marker for late stage PCa as its overexpression possess strong correlation with advancing tumor grade, stage, and progression to androgen independence [ 37 ]. In addition, it anchors to cancer cell surface without exocytosis and therefore it is considered as a highly suitable target antigen for PCa immunotherapy [ 38 ]. PSP94, also known as prostatic inhibin or β-micro semino protein is one of the most abundant proteins in semen along with PSA and PAP.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, PSCA is considered as an effective marker for late stage PCa as its overexpression possess strong correlation with advancing tumor grade, stage, and progression to androgen independence [ 37 ]. In addition, it anchors to cancer cell surface without exocytosis and therefore it is considered as a highly suitable target antigen for PCa immunotherapy [ 38 ]. PSP94, also known as prostatic inhibin or β-micro semino protein is one of the most abundant proteins in semen along with PSA and PAP.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that this PSCA‐based vaccine can induce long‐term protection against PCa development in PCa‐prone transgenic adenocarcinoma mouse prostate mice and reported that vaccination induced MHC Class I expression and cytokine production (IFN‐γ, tumor necrosis factor‐A, interleukin 2 [IL‐2], IL‐4, and IL‐5) within prostate tumors. In the other study, Mai et al constructed a fusion plasmid containing the PSCA gene and cytotoxic T‐lymphocyte associated antigen‐4 (CTLA‐4) and evaluated its antitumor effect in an animal model of PCa. Their study showed mice immunized with pVAX1‐PSCA‐F2A‐CTLA‐4 exhibited greatly increased secretion of the Th1 (IFN‐g) and Th2 cytokines (IL‐4).…”
Section: Discussionmentioning
confidence: 99%